On the insufficiencies of the current legislative regime regarding physician-patient mediation in the professional liability of physicians - Bek, Dominika (Medicine, law & society, 2023)
The article presents a critical opinion on physician-patient mediation conducted in the context of proceedings on the professional liability of physicians. The starting point is the Act on Medical Chambers, which provides for the possibility of conducting a mediation between the accused physician and the aggrieved patient. This regulation is unique in the region. Its specific measures, such as, for example, the choice of a mediator among physicians, have undergone a critical assessment in the literature. As a rule, the need for the functioning of mediation in the context of professional liability is not called into question. However, a thorough analysis of the assumptions of mediation and restorative justice and the function of professional liability of physicians suggests going a step further. Although the physician-patient conflict certainly requires conciliatory solutions, it seems that the disciplinary regime does not provide an adequate foundation for agreement because it is unable to secure the aggrieved person’s interests.
Keywords: človekove pravice; mediacija; mediation; medical chamber; pacienti; physician; Poljska; professional liability; restorative justice; zdravniki; zdravstvene napake